1997
DOI: 10.1289/ehp.97105216
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution and emergency room visits for asthma in Santa Clara County, California.

Abstract: During the winters of 1986-1987 through 1991-1992, rainfall throughout much of Northern California was subnormal, resulting in intermittent accumulation of air pollution, much of which was attributable to residential wood combustion (RWC). This investigation examined whether there was a relationship between ambient air pollution in Santa Clara County, California and emergency room visits for asthma during the winters of 1988-1989 through 1991-1992. Emergency room (ER) records from three acute-care hospitals we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
80
0
5

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(86 citation statements)
references
References 24 publications
1
80
0
5
Order By: Relevance
“…An increase of PM 10 results in a greater use of asthma medication, frequent visits to medical practitioners and increase of asthma-related hospital admissions (Schwartz et al, 1993;Lipsett et al, 1997;Peters et al, 1997;Atkinson et al, 1999;Norris et al, 1999, Delfino et al, 2002Maciejczyk et al, 2004, Monteil, 2008Yeatts et al, 2009;Scapellato et al, 2009). In these studies the association between asthma attacks and different triggers as such as PM 10 , ozone (O 3 ), nitrogen dioxide (NO 2 ), sulfur dioxide (SO 2 ), and carbon monoxide (CO) have been investigated.…”
Section: R Dimitrova Et Al: Relationship Between Particulate Mattermentioning
confidence: 99%
See 2 more Smart Citations
“…An increase of PM 10 results in a greater use of asthma medication, frequent visits to medical practitioners and increase of asthma-related hospital admissions (Schwartz et al, 1993;Lipsett et al, 1997;Peters et al, 1997;Atkinson et al, 1999;Norris et al, 1999, Delfino et al, 2002Maciejczyk et al, 2004, Monteil, 2008Yeatts et al, 2009;Scapellato et al, 2009). In these studies the association between asthma attacks and different triggers as such as PM 10 , ozone (O 3 ), nitrogen dioxide (NO 2 ), sulfur dioxide (SO 2 ), and carbon monoxide (CO) have been investigated.…”
Section: R Dimitrova Et Al: Relationship Between Particulate Mattermentioning
confidence: 99%
“…In these studies the association between asthma attacks and different triggers as such as PM 10 , ozone (O 3 ), nitrogen dioxide (NO 2 ), sulfur dioxide (SO 2 ), and carbon monoxide (CO) have been investigated. Some reported significant correlations between asthma-related hospital admissions and concentrations of PM 10 and NO 2 (Lipsett et al, 1997), PM 10 and SO 2 and/or SO 4 (Peters et al, 1997;Atkinson et al, 1999) or PM 2.5 or PM 10 and CO (Norris et al, 1999;Sheppard et al, 1999) whereas others, using multi-pollutant models, contend that asthma is related to PM concentrations only (Nauenberg and Basu, 1999;Tolbert et al, 2000). All studies that used single-pollutant models have reported significant association of particles and asthma admissions (Schwartz et al, 1992;Maciejczyk et al, 2004;Monteil, 2008;Scapellato et al, 2009).…”
Section: R Dimitrova Et Al: Relationship Between Particulate Mattermentioning
confidence: 99%
See 1 more Smart Citation
“…[11,12]. The response of airway cells to these stimuli is mediated through activation of distinct transmembrane signaling intermediates [13].…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies which link exposure to air pollution, and specifically particulate matter (PM), with increased morbidity and mortality due to respiratory illnesses, such as asthma 1 , 2 , 3 , 4 bronchiolitis 5 , 6 and chronic obstructive pulmonary disease 7 , 8 , 9 . These epidemiological studies generally focus on relating mortality and hospital admissions for respiratory or cardiac conditions to a broad range of “general” PM, including particles originating from soil and other natural sources, “road‐dust” from tyre and brake wear, and diesel exhaust particles (DEP).…”
Section: Introductionmentioning
confidence: 99%